Effect of crystallographic orientation and geometrical compatibility on fatigue crack initiation and propagation in rolled Ti-6Al-4V alloy. (15th September 2019) - Briffod, Fabien; Bleuset, Alexandre; Shiraiwa, Takayuki; Enoki, Manabu
Abstract: Fatigue crack initiation and short crack propagation was systematically investigated in a rolled α / β Ti-6Al-4V alloy through a combination of in situ optical microscopy observations during fully-reversed uniaxial fatigue experiments and post-mortem electron backscattering diffraction analyses. The effect of microstructural attributes (phase, crystal orientation, grain boundary) on fatigue crack formation and early growth was statistically quantified based on the analysis of a large dataset of grains. Crack initiation was mainly observed on prismatic slip systems which was related to the effect of the rolling texture. Crack propagation was found to be mostly transgranular and crystallographic on both basal and prismatic slip systems. An analysis of the effect of the β phase was proposed to explain the preferential slip systems for propagation in lamellar colonies. Crack deflection was quantified for a large set of grain boundaries. A combination of elastic, plastic and geometric compatibility criteria was identified to consistently predict the preferential slip systems for crack propagation across grain boundary. Finally, a discussion on the transition from microstructure-sensitive to microstructure-insensitive crack propagation was proposed. Graphical abstract: Image 1